The Role of Female Solidarity in Overcoming Patriarchal Structures in the Girl with the Louding Voice - Aprilian Risky Fajar Cholid; Maria Johana Ari Widayanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This paper analyzes the function of female solidarity in dismantling patriarchal hierarchies via a qualitative literary examination of Abi Dare's novel The Girl with a Louding Voice. The research examines how female solidarity functions as a means of empowerment in the context of systemic gender discrimination in modern Nigerian culture. The study examines the issues of entrenched patriarchal norms and the intersectional barriers encountered by women, specifically with socioeconomic position, cultural identity, and colonial legacies. The research aims encompass examining the dynamics of female connections in the novel and comprehending how these interactions enable resistance to patriarchal limitations. A qualitative investigation of prominent female characters and their interactions is conducted, utilizing intersectionality and postcolonial feminism as theoretical frameworks to attain these objectives. The primary findings indicate that female solidarity emerges in intricate, diverse forms, influenced by variations in class, age, and resource accessibility. Collective experiences of mentorship, emotional support, and communal care enable women to navigate and overcome patriarchal limitations. Furthermore, the novel underscores the dual nature of education—a legacy of colonialism—as both an instrument of oppression and emancipation. This research enhances feminist literary discourse by clarifying the dynamics of sisterhood in current Nigerian contexts and emphasizing its transformational potential for social change. The paper further examines the ramifications of these findings for wider feminist activity, highlighting the imperative of ongoing critical engagement with power relations within female networks. The limitations encompass the singular textual emphasis, indicating potential pathways for comparative analyses within African feminist literatures.